2017
DOI: 10.1590/1806-9282.63.04.311
|View full text |Cite
|
Sign up to set email alerts
|

Patient Concerns Inventory for head and neck cancer: Brazilian cultural adaptation

Abstract: Objective: The purpose of this study was to translate, culturally validate and evaluate the Patients Concerns Inventory -Head and Neck (PCI-H&N) in a consecutive series of Brazilian patients. Method: This study included adult patients treated for upper aerodigestive tract (UADT) cancer. The translation and cultural adaptation of the PCI-H&N followed internationally accepted guidelines and included a pretest sample of patients that completed the first Brazilian Portuguese version of the PCI. Use, feasibility an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 26 publications
0
6
0
4
Order By: Relevance
“…The findings are limited by the small sample size, which is reflective of the low oral cancer incidence in Malaysia [48]. Other similar studies also reported small sample sizes [36,[49][50][51]. In a period of 8 months, only 85 eligible patients agreed to participate in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…The findings are limited by the small sample size, which is reflective of the low oral cancer incidence in Malaysia [48]. Other similar studies also reported small sample sizes [36,[49][50][51]. In a period of 8 months, only 85 eligible patients agreed to participate in the present study.…”
Section: Discussionmentioning
confidence: 88%
“…Ao considerar que o câncer é um acontecimento inesperado, desencadeador de inúmeros sentimentos, tanto em clientes quanto familiares, os quais proporcionam sensações desagradáveis, por envolver situação nova, exige-se promoção da adaptação, de forma positiva ou negativa, seja ativa ou passiva. (9,10) Assim, cada indivíduo reage de modo particular, uma vez que são influenciados pelas próprias expectativas, história de vida e vivências cotidianas. Atrelado a este fato, todos os entrevistados relataram sentir-se bem e felizes, antes do adoecimento e das alterações na imagem corporal.…”
Section: Discussionunclassified
“…A tradução e adaptação cultural seguiram as mesmas diretrizes dos trabalhos anteriores e a aplicação da pré-versão final foi realizada em pacientes adultos tratados por câncer do trato aerodigestivo superior. Após a aplicação na amostra foram feitas alterações culturais, sugeridas pelos peritos e pelos autores do estudo, buscando maior aceitabilidade e viabilidade do IPP-CP na versão final 7 .…”
Section: Artigounclassified
“…As dúvidas foram discutidas com o autor do instrumento original e assim já poderiam fazer alterações necessárias após os resultados 14 . Com base na literatura disponível para este tipo de pesquisa, não há consenso nem critérios gerais para estabelecer o tamanho da amostra necessário para a aplicação dos pré-testes visando o entendimento dos instrumentos, mas uma amostra de pelo menos 50 a 100 participantes é geralmente recomendada 7 . A fim de avaliar a confiabilidade e a reprodutibilidade, a escala também pode ser aplicada pelo mesmo avaliador com intervalo de uma semana (análise intraobservador) e diferentes avaliadores no mesmo dia (análise interobservador) 15 .…”
Section: Artigounclassified